(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
India makes a lot of scrap tyres every year, which is bad for the environment. Recycling these tyres can help with these problems, and they can be used in many civil engineering projects, such as changing the way asphalt pavement is made. Using used rubber in asphalt mixtures has been studied a lot and shown to be possible. This work also looks into the possibility that used engine oil could be used to change bitumen in a way that is good for the environment and helps with problems related to getting older. When waste engine oil is added, problems arise, such as more rutting and less elasticity recovery. The focus of the research is on using waste materials, like CRMB waste and used engine oil, to replace some bitumen. The goal of the study is to make waste samples with different amounts of VG10 bitumen, waste engine oil, and waste CRMB. These concentrations range from 0% to 15%, which tells us a lot about how waste materials could be used to build roads.